Appropriation of Information in Data Visualization - Barizon Filho, Antonio Lucio; Cremonez Rosa, Pedro Henrique (InfoDesign, 2021)
The study seeks to understand which elements related to the process of appropriation of information are facilitated and supported by data visualization. Based on the understanding that appropriation of information encompasses the transmission of information and its learning by the user, the visual representation of the data, through graphic resources, assists in this process by synthesizing the information content in a clear manner, thus reducing abstractions. The study is based on a bibliographic survey of an explanatory character, trying to bring reflections on the importance of visualizing data in the process of appropriation of information.